2020
DOI: 10.1039/c9ta11708c
|View full text |Cite
|
Sign up to set email alerts
|

Using nanoconfinement to inhibit the degradation pathways of conversion-metal oxide anodes for highly stable fast-charging Li-ion batteries

Abstract: Nanostructured hybrids that physically encapsulate highly morphable, high capacity Li-ion battery anodes can potentially enable much longer cycle life than straightforward deployment of the same chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…A comparative study of NiO-based composites containing rGO at various oxidation degrees has shown that the functional groups on rGO affect the cycling behavior in lithium-half cells [35]. On the other hand, NiO trapping in hollow carbon structures and/or nanotubes as well as graphene papers may mitigate the electrode degradation and improve the cycle life [36][37][38], while core-shell morphologies may lead to a remarkable specific capacity [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative study of NiO-based composites containing rGO at various oxidation degrees has shown that the functional groups on rGO affect the cycling behavior in lithium-half cells [35]. On the other hand, NiO trapping in hollow carbon structures and/or nanotubes as well as graphene papers may mitigate the electrode degradation and improve the cycle life [36][37][38], while core-shell morphologies may lead to a remarkable specific capacity [31].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, hollow Ni/NiO nanospheres embedded in graphite sheets have been prepared by polymerization of a carbon precursor in presence of a nickel salt, pyrolysis at 800 °C to from metallic nickel embedded in a carbon matrix, and subsequent oxidation at 350 °C [30]. However, only a few works investigated the actual behavior of NiO anodes in lithium-ion cells [38][39][40] despite the great amount of literature on the conversion-anode performance in halfcell configuration [18][19][20][21][24][25][26][27]41,42], even though a detailed investigation in the full cell employing a conventional cathode, such as NCM, is considered to be essential to assess the actual applicability [4,43], particularly considering the abovementioned issues in terms of electrode stability upon cycling, working voltage and coulombic efficiency [9]. Therefore, we study herein, a NiO anode in a lithium-ion battery using the high-performance NCM layered cathode.…”
Section: Introductionmentioning
confidence: 99%
“…Ng et al have recently shown that the nanoconfinement of anodes made of metal oxide (MO) NPs, and their consequent isolation from the electrolyte, could eliminate the primary mechanisms of degradation and coulombic efficiency loss in MO anodes. 119 Therefore, NP assembly into SPs might yield self-assembled anodes with improved cycling stability, derived from their 3D nanostructure. For instance, by controlling the geometric configuration of mesoporous iron oxide SPs, Lee et al could achieve higher cycling stability than random aggregates of iron oxide NPs, thanks to the confinement of the stable solid–electrolyte interphase layer on the outer surface of the SP.…”
Section: Future Outlook and Conclusionmentioning
confidence: 99%
“…[1] However, safety and high cost are major concerns in Li-ion batteries, especially for emerging electric vehicle and grid storage applications, due to the use of flammable non-aqueous electrolytes and some toxic elements such as cobalt. [2][3][4] Among non-Li battery systems, Zn-based batteries have been touted as a promising option to compete with Li-ion batteries. Zn anodes have been a reliable electrode material in primary batteries since the 1960s due to their intrinsic safety, low cost of Zn metal and use of aqueous, nonflammable electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the solubility of zincate is limited, and once the saturation concentration of zincate is reached ZnO is formed via a dehydration reaction [Equation (2)]. The formed ZnO passivates the surface, creating an insulating layer of porous cubic-rod shaped ZnO structures that: 1) restricts the accessibility of the electrolyte to the active Zn surface; 2) increases the cell impedance; and 3) limits the cell capacity by reducing the Zn utilization.…”
Section: Introductionmentioning
confidence: 99%